Upfront Androgen Receptor-Axis-Targeted Therapies in Men with De Novo High-Volume Metastatic Hormone-Sensitive Prostate Cancer - Kimura, Natsuo; Kaneko, Yuki; Tetsuka, Takahiko; Takei, Akinori; Uchida, Takato; Abe, Hirokazu; Amiya, Yoshiyasu; Shima, Takayuki; Suzuki, Noriyuki; Hayashi, Satoru; Nakatsu, Hiroomi (Urology Journal, 2023)
Purpose: The extent of effectiveness of upfront androgen receptor-axis-targeted therapies (ARAT) versus total androgen blockade (TAB) in improving prostate cancer-specific survival (CSS) and progression-free survival (PFS) in a real-world sample of Japanese patients with high-volume mHSPC remains unclear. We, therefore, investigated the efficacy and safety of upfront ARAT versus bicalutamide for de novo high-volume mHSPC in Japanese patients. Material and Methods: This was a multicenter retrospective study that analyzed CSS, clinical PFS, and adverse events (AEs) in 170 patients with newly diagnosed high-volume mHSPC. Fifty-six patients were treated with upfront ARAT, and 114 of them were prescribed bicalutamide in addition to ADT between January 2018 and March 2021. The primary and secondary endpoints were CSS and PFS, respectively. A 1:1 nearest neighbor propensity score matching (PSM) with a caliper of 0.2 was performed to match the ARAT group to TAB patients. Results: During the follow-up for a median of 21.5 months, the median CSS was not reached and 37 months in the upfront ARAT and total androgen blockade (TAB) groups, respectively (log-rank test: P = 0.006) by propensity score matching (PSM). Moreover, while the PFS of ARAT was unreached, the median PFS of TAB was 9 months (log-rank test: P < 0.001). Nine patients discontinued ARAT owing to grade ≥ 3 AEs; one patient who was treated with TAB had a grade 3 AE. Conclusion: Upfront ARAT significantly prolonged the CSS and PFS of patients with high-volume mHSPC better than TAB, although ARAT was associated with a higher rate of grade ≥ 3 AEs. Upfront ARAT can be more beneficial for patients with de novo high-volume mHSPC than TAB.